2011
DOI: 10.1063/1.3549573
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer dynamics of model charge transfer centers of a multicenter water splitting dye complex on rutile TiO2(110)

Abstract: Charge transfer dynamics between an adsorbed molecule and a rutile TiO(2)(110) surface have been investigated in three organometallic dyes related to multicenter water splitting dye complexes: Ru 535 (cis-bis(isothiocyanato)bis(2,2'-bipyridyl-4,4'-dicarboxylato)-ruthenium(II)), Ru 455 (cis-bis(2,2'-bipyridyl)-(2,2'-bipyridyl-4,4'-dicarboxylic acid)-ruthenium(II)), and Ru 470 (tris(2,2'-bipyridyl-4,4'-dicarboxylic acid)-ruthenium(II)). The adsorption of the dye molecules on the rutile TiO(2)(110) surface has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 47 publications
6
34
0
Order By: Relevance
“…It was found that charge transfer from N3 dye specific unoccupied orbitals, which is located on bis‐isonicotinic acid ligands, to substrate occurs in less than 16 fs considering the similar covalent Ti‐O bonding geomery, whereas charge transfer from unoccupied orbitals localized at the central Ru atom or thiocyanate ligands is longer due to weaker electronic coupling . For N3 derivatives in which bis‐isonicotinic or thiocyanate ligands were substituted, the upper limit on charge transfer times either increases from 12 fs for N3 dye to 17∼21 fs or decreases to 0.9∼5.9 fs . Consequently, understanding the dependence of charge transfer times on different sites or ligand substitution provides imporant insights to tuning the charge transfer dynamics at dye/TiO 2 interfaces by engineering the electronic structures and binding geometries of dyes.…”
Section: Charge Transfer Dynamics At Organic/electrode Interfacesmentioning
confidence: 99%
“…It was found that charge transfer from N3 dye specific unoccupied orbitals, which is located on bis‐isonicotinic acid ligands, to substrate occurs in less than 16 fs considering the similar covalent Ti‐O bonding geomery, whereas charge transfer from unoccupied orbitals localized at the central Ru atom or thiocyanate ligands is longer due to weaker electronic coupling . For N3 derivatives in which bis‐isonicotinic or thiocyanate ligands were substituted, the upper limit on charge transfer times either increases from 12 fs for N3 dye to 17∼21 fs or decreases to 0.9∼5.9 fs . Consequently, understanding the dependence of charge transfer times on different sites or ligand substitution provides imporant insights to tuning the charge transfer dynamics at dye/TiO 2 interfaces by engineering the electronic structures and binding geometries of dyes.…”
Section: Charge Transfer Dynamics At Organic/electrode Interfacesmentioning
confidence: 99%
“…The multilayer data were combined with data obtained in previously published experiments of N3. 17,20 All measurements were performed at room temperature. XPS data were calibrated to the Fermi edge.…”
Section: Methodsmentioning
confidence: 99%
“…17 We have also previously reported the charge transfer interaction of N3 and its bi-isonicotinic acid ligand on Au(111) 18,19 and N3 as well as related water splitting molecules on TiO 2 . 17,20,21 The upper limit for the charge transfer time from N3 to Au(111) and TiO 2 was 4.4 fs 18 and 12 fs, 20 respectively. In order to further develop DSSCs, it is important that we understand the subtle bonding and electronic properties that lead to efficient photon to current efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] However, it is unclear whether the behavior of dye molecules on a single crystal surface is faithfully reproduced by molecules on nanocrystalline TiO 2 , which is the material used for photovoltaic cell electrodes. Direct observations are very difficult because of the complex structure of nanocrystalline TiO 2 , so a high-resolution method with high specificity is required for observing the microscopic structure of the surface morphology of these porous materials.…”
Section: Introductionmentioning
confidence: 99%